Analisis dan Perancangan ROP, EOQ, Safety Stock Sistem Pengendalian Persediaan Bahan Baku Pada Rumah Makan Bubur Ayam Citarasa - Intishar Ghinawijaya Katiandagho; Rendra Trisyanto (Indonesian Accounting Literacy Journal, 2021)
Inventory is the most crucial aspect in restaurant business, good control is needed so that operational activities can run smoothly. In ‘RM Bubur Ayam Citarasa’, the quantity of raw material inventory purchased is based on estimates and intuition so that the inventory costs incurred are not efficient. The purpose of this study is to find out the economical order quantity for each raw material, how much safety stock should be provided and when reordering should be done. The type of data used is quantitative data and is equipped with qualitative data which is then analyzed using the EOQ, Safety Stock and Reorder Point formula. As a result, the company could save Total Inventory Costs for it’s twelve raw materials up to Rp2,290,219 with the EOQ Method. In order for the quantity of raw material can be monitored properly, researcher designed a simple inventory application using Ms. Excel.